Islamophobia and Radicalization Breeding Intolerance and Violence - Esposito, John L.; Iner, Derya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
While the themes of radicalization and Islamophobia have been broadly addressed by academia, to date there has been little investigation of the crosspollination between the two. Is Islamophobia a significant catalyst or influence on radicalization and recruitment? How do radicalization and Islamophobia interact, operate, feed one another, and ultimately pull societies toward polar extremes in domestic and foreign policy? The wide-ranging and global contributions collected here explore these questions through perspectives grounded in sociology, political theory, psychology, and religion. The volume provides an urgently needed and timely examination of the root causes of both radicalization and Islamophobia; the cultural construction and consumption of radical and Islamophobic discourses; the local and global contexts that fertilize these extreme stances; and, finally, the everyday Muslim in the shadow of these opposing but equally vociferous forces.
Introduction: Theoretical Discussion and Empirical Findings -- Part I: Co-radicalization -- 1. Ironies of scapegoating: From Islamophobia to Radicalization (Michael Welch) -- 2. Religious Extremism and Islamophobia: A Problem of Reactive Co-radicalization? (Douglas Pratt) -- 3. How Islamophobes are Reproduced and Radicals Responded to the Halal Debate in Australia: Let's Feed Radicals with the Halal (Derya Iner) -- Part II: The Crosspollination of Radicalization and Islamophobia: Local and Global Factors -- 4. Can Islamophobia in the Media Serve the Islamic State Propaganda? The Australian Case, 2014-2015 (Nahid Kabir) -- 5. Morocconization of Dutch Islamophobia and the Increase of Radicalism among the Moroccan Dutch (Sam Cherribi) -- 6. Radicalization and Islamophobia as a Global Management Failure in Syria (Radwan Ziadeh) -- Part III: Countering Terrorism with Islamophobia -- 7. How Counterterrorism Radicalizes: Exploring the Nexus between Counterterrorism and Radicalization (Haroro Ingramand Kriloi Ingram) -- 8. Deepening Divides? Implementing Britain's "Prevent" Counterterrorism Program (Paul Thomas) -- 9. When the 'Right Thing to Do' Feels So Wrong: Australian-Muslim Perspectives on 'Intimates' Reporting to Authorities about Violent Extremism (Michelle Grossman) -- Part IV: The Products of Radicalization and Islamophobia -- 10. Historically Reproduced Muslim as a "Subject" of Islamophobia and Radicalization (Katy Naban) -- 11. Muslim: Islamophobic and radical discourse: A Driving Force for Muslim Active Citizenship (Mario Peucker) -- 12. Activist Muslims and the Hizmet Movement: Can Islamophobia and Islamic Extremism be Addressed at the Same Time? (Ihsan Yilmaz and Ismail Sezgin).
Keywords: Sociology; Political sociology; Terrorism; Political violence; Religion and sociology; Criminology; Culture; Sociology; Political Sociology; Terrorism and Political Violence; Sociology of Religion; Crime Control and Security; Sociology of Culture